Essentials of TQM - Morehouse, Debra L. (Gower, 1996)
Properly implemented, Total Quality Management (TQM) can dramatically change the way business is done. This work provides an understanding of the thinking behind this management philosophy, its key concepts, and advice on how to take it forward in an organization.